Answer:
Step-by-step explanation:
Givens
Let a = the first number
Let b = the second number
Equations
a + b = 39
b = 1/2 * a + 6
Put the second equation into the first one
a + 1/2 * a + 6 = 39 Simplify the left.
(3/2)a + 6 = 39 Subtract 6 from both sides
(3/2)a + 6 - 6 = 39 - 6 Combine
(3/2)a = 33 Multiply both sides by 2
3a = 33*2
3a = 66 Divide both sides by 3
3a/3 = 66/3
a = 22
b = 1/2 a + 6
a = 22
b = 1/2 * 22 + 6
b = 11 + 6
b = 17
Check
22 + 17 = 39
<span>A.) y = 0.3(2)x
These are exponential decay</span>
Answer:
D = 90°
E = 147°
F = 33°
Step-by-step explanation:
E:
E is 147°, because it is vertical to the angle 147°
F:
F is 33°, because 147* is its supplementary angle, or angles that add up to 180°
D:
D is worth 90°, because its supplement is worth 90°
-Chetan K
Answer:
The simplest ratio would be 5:3
Step-by-step explanation:
Both 10 and 6 can be divided by 2.
They turn into 5 and 3.
Since you can't make 5 and 3 any smaller, this will be the answer.
5:3
Hope this helped! :D